Introduction of the Project “Community Police Officer” as a Step towards Strengthening Local Security Infrastructure (Law and Safety, 2020)
The author has emphasized on the importance of strengthening the institutional capacity of local self-government agencies to address their challenges, including in the field of public safety, in particular by strengthening local security infrastructure. It has been stated that the urgent issue of the present time is to update the tools of interaction between the local population and the police to achieve a common goal – to ensure public order and safety at the regional level focused on the needs of citizens. It has been emphasized that it is currently important to use the positive foreign experience of organizing the work of the police agencies and units. On the basis of studying this experience it is advisable to implement pilot projects aimed at creating a safe environment for citizens, which should implement effective local security infrastructure. To this end, the project “Community Police Officer” was launched in 2019 as part of the reform of the National Police in Ukraine.Particular attention has been paid to the fact that the main purpose of the project “Community Police Officer” is to ensure close cooperation between police officers and amalgamated community, where police activities are primarily focused on the needs of the community. It has been argued that a characteristic feature of the project “Community Police Officer” is the focus on the introduction of a qualitatively and meaningfully new format of policing, where the needs of the community, local population should be in priority, which should be studied and ensured by keeping constant contacts between police officers and local population. The main innovations of this project have been analyzed. The powers of the community police officer and the district police officer have been differentiated. The key stages of the project “Community Police Officer” have been outlined. Specific features of training community police officers have been characterized, since it directly affects the effectiveness of their duties and the state of public order and safety within a particular amalgamated community. The peculiarities of evaluating the effectiveness of the community police officer’s work have been revealed. The author has emphasized on the importance of developing Regulations on the organization of community police officers’ work and developing an effective mechanism for elaborating the training programs for community police officers.
Keywords: police; community police officer; amalgamated community; local safety infrastructure; public order; public security